A cost-effectiveness analysis of risk-based intervention for prevention of cardiovascular diseases in IraPEN program: A modeling study - Jamshidi, Amirparviz; Daroudi, Rajabali; Aas, Eline; Khalili, Davood (Frontiers in Public Health, 2023)
Background: IraPEN, a program developed in Iran based on the World Health Organization (WHO) package of essential noncommunicable (PEN) disease interventions for primary health care, was launched in 2015. Preventive interventions for cardiovascular diseases (CVD) are based on the level of risk calculated using the WHO CVD-risk chart. Objective: The main objective of this study is to measure the potential cost-effectiveness (CE) of IraPEN preventive actions for CVD in comparison with the status quo. Methods: A cost-effectiveness (CE) analysis from a healthcare perspective was conducted. Markov models were employed for diabetic and non-diabetic individuals, separately. Based on the WHO CVD risk chart, four index cohorts were constructed as low (<10%), moderate (10-19%), high (20-29%), and very high-risk (>=30%). Life years (LY) gained and quality-adjusted life years (QALY) were used as the outcome measures. Results: The intervention yields an incremental cost-effectiveness ratio (ICER) of 804, 551, and -44 for moderate, high, and very high CVD risk in non-diabetic groups, respectively. These groups gained 0.69, 0.96, and 1.45 life-years respectively from the intervention. The results demonstrated an ICER of 711, 630, -42, and -71 for low, moderate, high, and very high-risk groups with diabetes, respectively, while they gained 0.46, 1.2, 2.04, and 2.29 years from the intervention. Conclusion: The IraPEN program was highly cost-effective for all CVD risk groups in the non-diabetic individuals except the low-risk group. The intervention was cost-effective for all diabetic patients regardless of their CVD risk. The results demonstrated that the program can be cost-saving in high-risk groups.